Efektivitas Hukum dalam Penyidikan Tindak Pidana Penganiayaan yang Mengakibatkan Kematian Anak Binaan dengan Otopsi Forensik - Ida Septiani Anjelika; Heni Siswanto; Rini Fathonah (Lembaga Pengembangan Kinerja Dosen, 2025)
Law enforcement cannot be separated from the use of various sciences, one of which is forensic medicine. Its use is by implementing forensic autopsies for the purposes of investigating victims in unnatural and suspicious deaths that are suspected of being related to criminal acts such as in cases of alleged criminal acts of abuse that cause death. This study uses an empirical legal approach by reviewing applicable legal regulations and their application in practice. Data were obtained through interviews with investigators, forensic doctors, and the victim's family, as well as literature studies that include laws and previous research. The results of the study indicate that forensic autopsies have an important role in investigating cases of abuse that cause death, as occurred in the case of the death of a foster child at LPKA Bandar Lampung. The autopsy results revealed signs of previously undetected physical violence, allowing law enforcement officers to name suspects and continue the investigation process. However, the implementation of autopsies in the Indonesian legal system still faces various obstacles, including resistance from the victim's family who refuse autopsies due to cultural and religious factors, limited forensic experts and autopsy facilities in several areas, and intervention from certain parties who try to hinder the investigation. Therefore, this study recommends a stricter policy in requiring autopsies for suspicious deaths, increasing the number of forensic personnel, and transparency in the legal process to ensure justice for victims and families. Thus, autopsies can function optimally as scientific evidence in revealing criminal acts and strengthening law enforcement in Indonesia.